Exploring biodiversity in riparian corridors of a Mediterranean island: Plant communities and environmental parameters in Cyprus rivers. (2nd January 2016) - Papastergiadou, E.; Stefanidis, K.; Dorflinger, G.; Giannouris, E.; Kostara, K.; Manolaki, P.
Abstract : Riparian corridors are among the most sensitive ecosystems in the Mediterranean as they are significantly altered by human interventions. In this study, we explored the composition patterns of the aquatic vegetation in 17 rivers of Cyprus. Hierarchical clustering and detrended correspondence analysis were conducted in order to distinguish plant community types among the river sites. The permanent flow sites (R-M4) were divided into three types and characterized mostly by the presence of Brachythecium rivulare, Nasturtium officinale, Veronica anagallis-aquatica and Lemanea sp. The temporary flow sites (R-M5) presented higher heterogeneity and species richness. In temporary rivers, three community types were also identified. Both diversity indices and compositional variation differed among the community types. Canonical correspondence analysis was performed between the aquatic vegetation patterns and the environmental attributes. The results revealed that human influence is the most important descriptor of the aquatic vegetation in both permanent and intermittent rivers. Activities that are connected with disturbance of the water flow (water abstraction, dam influence and stream hydrology) appeared to play a key role in determining the aquatic plant communities. Overall, the results of this study can provide useful information towards the development of an effective management plan for the river basins of Cyprus.